Inside Debt and Economic Growth: A Cambridge - Kaleckian Analysis - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
Inside debt is a fundamental feature of capitalist economies. This paper examines the growth effects of consumer and corporate debt using a Cambridge - Kaleckian growth framework. According to the Cambridge - Kaleckian model inside debt has an ambiguous effect on growth. This is counter to the intuition of static short-run macro models in which higher debt levels lower economic activity and shows intuitions derived from short run macroeconomics do not always carry over to growth theory. Growth is faster in endogenous money economies than in pure credit economies, ceteris paribus. That is because lending in endogenous money economies creates money wealth that increases spending and lowers saving. Interest payments from debtors to creditors are a critical channel whereby debt affects growth. In the consumer debt model this interest transfer mechanism exerts a negative influence on growth. However, in the corporate debt model the transfer can raise growth if the marginal propensity to consume of creditor households exceeds the marginal propensity to invest of firms.
urn:nbn:de:101:1-2009071357
Keywords: E12; O40; 330; Growth; Debt; Interest transfers; Cambridge distribution theory; Kaleckian growth theory.